Exploring the Differences in Pay-What-You-Want Pricing between Products and Services: Interactive Effects of Product Knowledge, Social Visibility and Tangibility - Roy, R.; Rabbanee, Fazlul; Sharma, Piyush (2016)
Pay-what-you-want (PWYW) is a unique participative pricing mechanism in which the buyers can pay nothing or pay any price they want and the seller has to accept it without being able to withdraw the offer (Kim et al., 2009, 2014). Prior research on PWYW pricing, focuses on the direct and interactive effects of several individual and situational variables, such as altruism, price consciousness and fairness perceptions (Kim et al., 2009), involvement level (Roy 2015), internal reference prices (Roy et al. 2016a), external reference prices, social visibility and purchase motivation (Roy et al. 2016b). However, most of these studies were conducted in popular service contexts such as restaurant, cinema and delicatessen (Kim et al., 2009, 2014; Roy et al. 2016a,b). Hence, it is not clear if and to what extent the mechanism by which consumers decide how much to pay in a PWYW setting, is similar or different between the products and services contexts. Similarly, recent studies examine the role of product involvement and social visibility in PWYW decision-making process but ignore other variables such as consumer knowledge and product/service characteristics. We address both these gaps with a new conceptual model that incorporates direct and interactive effects of consumer knowledge, social visibility and tangibility as the independent variables and the allocation of internal reference prices into the prices that the consumers are willing to pay as the dependent variable, while controlling for involvement level. We use a lab experiment with undergraduate students to test our hypotheses and report our findings in this paper.